Padaleman Karuhun and Songko as Indigenous Spatial Planning Logic: A Phenomenological Study - Imam Indratno; Ina Helena Agustina; Sugih Dinul Yakin; M. Ari Fandi; Deshinta Arova Dewi (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2026)
Across Southeast Asia, indigenous settlements are not merely places of habitation but living spatial systems in which moral order, ecological ethics, customary authority, and intergenerational knowledge are embedded in everyday practices. Yet these systems remain insufficiently recognized in contemporary settlement planning, heritage conservation, and customary land governance, where interventions frequently privilege technocratic approaches over locally embedded spatial knowledge. This study examines Kampung Adat Kuta (West Java) and Nagari Panti Selatan (West Sumatra): the former a vertically organized sacred-ecological system rooted in Sundanese cosmology, the latter a horizontally structured socio-institutional system grounded in Minangkabau matrilineal tradition. Using a comparative qualitative approach grounded in Alfred Schutz’s phenomenology, the research integrates in-depth interviews, participant observation, ritual documentation, and cultural mapping to examine how indigenous spatial meanings are produced, institutionalized, and transmitted across generations. The analysis shows that Inget Karuhun, Padaleman Karuhun, and Songko function not merely as cultural symbols but as indigenous spatial planning logics: Padaleman Karuhun organizes a settlement through a vertically integrated sacred-ecological hierarchy governed by ritual obligation and ancestral norms, while Songko structures a settlement through a horizontally integrated socio-spatial system based on matrilineal governance, communal institutions, and symbolic authority. These findings extend planning scholarship by showing that indigenous settlements embody coherent systems relevant to settlement planning, heritage conservation, and customary land governance, and propose indigenous spatial planning logic as an ontological planning perspective that recognizes indigenous settlements as living planning systems rather than cultural landscapes or heritage objects.